Education for Students Regarding Legal Sanctions for Bullying Perpetrators as an Effort to Prevent Violence in Schools - Hilda, Hilda; Asriyani, Asriyani; Utami, Fidyah Faramita; Achmad, Andi Nurul Isnawidiawinarti; Qalbi, Vivi Nur (AIWADTHU: Jurnal Pengabdian Hukum, 2026)
Introduction: Bullying at school, whether physical, verbal, nonverbal, or through information and communication technology media, is a form of violence according to the Minister of Education and Culture Regulation of Education and Culture No. 46 of 2023 concerning the Prevention and Handling of Violence in the Educational Environment. Bullying at a certain level can be categorized as a criminal offense, which can result in legal consequences in the form of criminal sanctions. Efforts to prevent and handle bullying in schools must be carried out to protect students from such legal consequences.Purposes of The Devotion: to raise students' legal awareness (legal culture) regarding forms of bullying and the criminal penalties that can be imposed for such acts in order to create a safe and enjoyable school environment that ensures a quality learning process.Method of The Devotion: The method used to carry out the activity was legal counseling. This counseling activity took the form of lectures by a team of counselors who presented the material through audio-visual and presentation media and opened up interactive dialogue between the students and the counseling team through question and answer sessions.Results Main Findings of the Devotion: Bullying is a criminal offense. Students in primary and secondary education who engage in bullying at school are subject to criminal sanctions under applicable law. One of the efforts to prevent bullying in schools is through education in the form of legal counseling for students.